Gorska območja Furlanije-Julijske krajine med socialno in gospodarsko izključenostjo ter novimi poselitvenimi modeli. Ali gre za inverzijo trenda? - Džajić Uršič, Erika (Geografski vestnik, 2023)
This article aims to demonstrate that migration phenomena improve the appearance and socio-economic position in the Friuli-Venezia Giulia mountain areas. In this area, mountain villages have been suffering from a long-term decline in population, economic activity, deteriorating infrastructure, decreasing services, and social isolation for almost half a century (since the 1950s). These depopulated villages are also referred to as »ghost villages«. However, the trend is now reversing, as evidenced by this research. The study is based on an analysis of the current situation, official statistical data, and primary data from interviews conducted in the area. The results show that newcomers bring innovations in agriculture, tourism, arts, and culture and play a key role in renovating existing structures, reusing land, and establishing a creative dynamic. Their activities increasingly enable the regeneration and maintenance of alpine cultural landscapes, resulting in the emergence of new social and agricultural structures with novel farming practices. The processes of regeneration may serve as a good practice example for other partially abandoned settlements in mountain areas.
Keywords: amenity migration; Friuli-Venezia Giulia; Furlanija-Julijska krajina; geografija; geography; ghost villages; gorska območja; Italija; Italy; migracije; migrations; mountains; revitalizacija; revitalization planning; selitev zaradi kakovosti življenja; social and economic exclusion; socialna in gospodarska izključenost; vasi duhov